Corrosion prevention through performance optimization of biological cathodic protection system - Azman, Anis Fitri Afira (2021)
Unprotected pipelines, whether exposed to the air, submerged in seawater or buried underground are susceptible to corrosion and this phenomenon has been identified as one of the major mechanism that affects failures in oil and gas pipelines. At present, impressed current cathodic protection (ICCP) system is one of the methods used to control the corrosion of the steel pipeline. In this study, a new system was developed based on ICCP namely biological cathodic protection (CP) system. This system used the concept of microbial fuel cells (MFCs) to generate a protective current to the cathode (pipe). Little to know on the effect of both hydraulic retention time (HRT) and electrode surface area to anode-compartment volume ratio (ESAVR) simultaneously on the voltage output particularly for biological CP system. Therefore, this study analysed the optimum value of HRT and ESAVR of the biological CP system in generating adequate protective current for the carbon steel pipe with respect to copper/copper sulfate (Cu/CuSO4) reference electrode which is -850 mV. Optimization of these two parameters on the biological CP system was done using response surface methodology based on central composite design (CCD) approach. CCD predicted values and experimental results showed a strong agreement, with an R2 value of 0.7953. The estimated optimal conditions for HRT and ESAVR of anode were at 9.21 h and 0.239 cm2/cm3 respectively. Consequently, the polarization study was conduted to determine the main limiting factors that occurred in the system. It was found that the main losses that occurred was due to the concentration losses whilst the maximum power point recorded was 1.1908 mW/cm2 (Run 11). The methodology supporting the purpose of this study by providing protective current to carbon steel pipe and thus verified the ability of this system to protect the pipe from corrosion.